2010
DOI: 10.1186/1471-2229-10-179
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric localization of Arabidopsis SYP124 syntaxin at the pollen tube apical and sub-apical zones is involved in tip growth

Abstract: BackgroundThe continuous polarized vesicle secretion in pollen tubes is essential for tip growth but the location of endo- and exocytic sub-domains remains however controversial. In this report we aimed to show that Arabidopsis thaliana syntaxins are involved in this process and contribute to spatially define exocytosis and membrane recycling.ResultsUsing GFP-fusion constructs, we imaged the distribution of pollen-specific (AtSYP124) and non-pollen syntaxins (AtSYP121 and AtSYP122) in transiently transformed N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 47 publications
5
58
0
Order By: Relevance
“…Conversely, based on colabeling with FM1-43 and FM4-64, it was concluded that exocytosis takes place in a subapical collar located in the transition zone between the tip and the shank, as well as at the shank, but not at the tip (Bove et al, 2008;Zonia and Munnik, 2008). In agreement, the pollen tube-specific syntaxin GFP-SYP124 was observed in the inverted cone, 10 to 25 mm away from the tip (Silva et al, 2010), and fluorescence recovery after photobleaching experiments with FM dyes also have indicated that exocytosis takes place at the subapical region (Bove et al, 2008;Moscatelli et al, 2012;Idilli et al, 2013). Yet, based on pollen tube reorientation experiments in a microfluidics device, it was concluded that growth takes place at the tip rather than at a subapical collar located in the transition zone between the apex and the shank (Sanati Nezhad et al, 2014).…”
supporting
confidence: 52%
“…Conversely, based on colabeling with FM1-43 and FM4-64, it was concluded that exocytosis takes place in a subapical collar located in the transition zone between the tip and the shank, as well as at the shank, but not at the tip (Bove et al, 2008;Zonia and Munnik, 2008). In agreement, the pollen tube-specific syntaxin GFP-SYP124 was observed in the inverted cone, 10 to 25 mm away from the tip (Silva et al, 2010), and fluorescence recovery after photobleaching experiments with FM dyes also have indicated that exocytosis takes place at the subapical region (Bove et al, 2008;Moscatelli et al, 2012;Idilli et al, 2013). Yet, based on pollen tube reorientation experiments in a microfluidics device, it was concluded that growth takes place at the tip rather than at a subapical collar located in the transition zone between the apex and the shank (Sanati Nezhad et al, 2014).…”
supporting
confidence: 52%
“…These membrane proteins include the SNARE (Soluble N-ethylmaleimide-sensitive factor attachment protein receptors) proteins, which mediate intracellular vesicle trafficking, fusion and secretion in plant growth and development and are also involved in ABA signaling pathway and in abiotic stress response (Leyman et al, 1999;Zhu et al, 2002;Leshem et al, 2006;Zhang et al, 2007b;Bassham and Blatt, 2008;Ebine et al, 2008;Grefen and Blatt, 2008;Sokolovski et al, 2008;Zouhar et al, 2009;Shirakawa et al, 2010;Silva et al, 2010). Another membrane trafficking protein, Rab7, a member of the Rab family of small GTPases which in yeast and mammals controls intracellular vesicle trafficking from the late endosome to the vacuole (Rutherford and Moore, 2002;Woollard and Moore, 2008), has been reported to be involved in salt and osmotic stress response in plants (Mazel et al, 2004;Agarwal et al, 2008;George and Parida, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The functional specificity is characteristic of several SNAREs belonging to multigenic families (Silva et al, 2010) and is generally related to regulated processes. The interesting distribution pattern of the deletion mutant GFP:At51H3, labelling small vacuolar compartments well separated from the central vacuole, indicates the possibility to delay the fusion process.…”
Section: Discussionmentioning
confidence: 99%